Comparative analysis of gnathostome Otx gene expression patterns in the developing eye: implications for the functional evolution of the multigene family. - Plouhinec, J; Leconte, L; Sauka-Spengler, T; Bovolenta, P; Mazan, S; Saule, S (2005)
We have performed a detailed analysis of the expression pattern of the three gnathostome Otx classes in order to gain new insights into their functional evolution. Expression patterns were examined in the developing eye of a chondrichthyan, the dogfish, and an amniote, the chick, and compared with the capacity of paralogous proteins to induce a pigmented phenotype in cultured retina cells in cooperation with the bHLH-leucine zipper protein Mitf. This analysis indicates that each Otx class is characterized by highly specific and conserved expression features in the presumptive RPE, where Otx1 and Otx2, but not Otx5, are transcribed at optic vesicle stages, in the differentiating neural retina, where Otx2 and Otx5 show a conserved dynamic expression pattern, and in the forming ciliary process, a major site of Otx1 expression. Furthermore, the paralogous proteins of the dogfish and the mouse do not display any significant difference in their capacity to induce a pigmented phenotype, suggesting a functional equivalency in the specification and differentiation of the RPE. These data indicate that specific functions selectively involving each Otx orthology class were fixed prior to the gnathostome radiation and highlight the prominent role of regulatory changes in the functional diversification of the multigene family.